Transesterification Studies on Avocado Seed Oil Using Carbon Supported CuO Nano Catalyst: Rate Kinetics and Thermodynamic Aspects. (25th July 2022) - Sasikumar, Bashyam; Jeevanandam, Prabahar; Samikkannu, Venkatesh Babu; Veeramalini, J. B.
Abstract : This study focused on the production of biodiesel using avocado seed oil (ASO) through esterification of free fatty acids (FFA) in the presence of carbon supported CuO nanoparticles (CuO/C). ASO was obtained using hexane as a solvent by Soxhlet extraction. Further characterization of ASO revealed that the oil had 8.2-10.2% (±0.2%) of FFA content. Using a two-step technique, the FFA content was decreased below 1% through esterification using a catalyst prepared from carbon supported nanoparticles of CuO. Additionally, CuO/C catalyst was characterized by different techniques, such as XRD and BET. From the investigations, the optimal time for the esterification process was found to be 6 h at 673 K. The use of carbon supported CuO nanoparticle for the transesterification process of ASO has not been attempted in earlier. Also, the studies on FFA present in the avocado seed oil had a significant outcome in this investigation. Further, the data observed from the reactions conducted at different temperatures were subjected for kinetic analysis to determine the reaction rate and thermodynamic study for activation energy.